Quality Indicators of Business Logistics and Supply Chain Management Education - Mikova, Stilyana (Research Papers, 2020)
Quality indicators are a key instrument for adequate decision-making about the direction and way of improving the education service. The aim of the study is to evaluate and select suitable quality indicators of Business Logistics and Supply Chain Management (BL/SCM) education through study of the opinions of three groups of respondents – university instructors, scientists and representatives of business. The results show that key quality indicators of education in the field of BL/SCM are: provision of an education that is practical-oriented and tied to the needs of the labour market; existence of stable partnerships with the business and science; and professional realisation of the students through internship programmes and projects.
Keywords: Logistics; Supply chain management; Education quality; Indicators